Interventions among male clients of female sex workers in Benin, West Africa: an essential component of targeted HIV preventive interventions. Issue 7 (17th October 2007) - Lowndes, C M; Alary, M; Labbé, A-C; Gnintoungbè, C; Belleau, M; Mukenge, L; Meda, H; Ndour, M; Anagonou, S; Gbaguidi, A
Abstract : Objectives: To assess the impact of interventions targeted towards female sex workers (FSWs) and their male clients on client HIV/STI prevalence and sexual behaviour. Methods: From 1993 to 2006, an HIV/STI preventive intervention focusing on condom promotion and STI care was implemented among FSWs in Cotonou, Benin, and then expanded to cover their male sexual partners in 2000. The interventions were scaled up to five other cities of Benin in 2001–2002. Serial cross-sectional surveys of HIV/STI prevalence and sexual behaviour were carried out among clients in Cotonou in 1998, 2002 and 2005; and in the five other cities (O/Cotonou) in 2002 and 2005. Results: Significant declines in gonorrhoea prevalence among clients of FSWs: Cotonou, from 5.4% in 1998 to 1.6% in 2005; O/Cotonou: from 3.5% in 2002 to 0.59% in 2005. Chlamydia prevalence also declined O/Cotonou, from 4.8% to 1.8%, while HIV prevalence remained stable. Reported condom use by clients with both FSWs and casual non-FSW partners, but not regular partners, increased significantly. While condom use at last sex with an FSW was similar in Cotonou to O/Cotonou around the time of implementation of the interventions (56% in 1998 vs 49% in 2002, respectively), it had risen to similar levels by 2005 (95% and 96%, respectively). Conclusions: These results demonstrate that it is possible to implement preventive and clinical services for clients of FSWs, and suggest that such interventions, integrated with those targeted towards FSWs, can have a significant effect on sexual behaviour and STI prevalence (particularly gonorrhoea) among this population.